An MRT Extension to the Multigrid Lattice Boltzmann Method (Communications in Computational Physics, 2019)
A full approximation storage multigrid method has been shown to improvethe convergence properties of the D2Q9 BGK lattice Boltzmann method [14]. In thispaper we extend the method to the multiple relaxation time collision model due to itsimproved stability. The new method is validated using Poiseuille flow. The methodis then extended to three dimensions. The efficiency of the V-cycle and W-cycle multigrid schedules and the under-relaxed Jacobi and Gauss Seidel multigrid smoothers arereported for the two and three dimensional models for lid driven cavity flow.
Keywords: Lattice Boltzmann method; multiple relaxation time; multigrid; full approximation storage multigrid.